Pengaruh Model Pembelajaran Kooperatif Tipe Number Heads Together Terhadap Aktivitas Dan Hasil Belajar Peserta Didik - riska riska; Fauziah Fauziah; Ahmad Ridoh (CV. DIGITIAL EDUKASI NUSANTARA, 2025)
Abstract Study This aim Forknow (1) influence use of learning models Cooperative type Number Heads Together to Activity learning, (2) use of learning models Cooperative type Number Heads Together towards learning outcomes Informatics, and (3) use of learning models Cooperative Number Head Together type against Activities and Learning Outcomes participant educate Class VII Informatics at SMP N 5 Muara Bungo. Methods used in study This is method study experiments, with amount sample 44. Data collection techniques using questionnaire techniques, tests questions, and documentation. And the data analysis techniques used in study This is a validity test, reliability test, power test discriminan, difficulty level test, normality test, homogeneity test, and hypothesis test. Based on the independent t-test on the activity Study obtained sig. value 0.000 < 0.05 and t count 5.358 > t table 2.018 and independent t-test on the results Study obtained sig. value 0.000 < 0.05 and t count 6.531 > t table 2.018. So it can be concluded that: There is an influence of the learning model cooperative type Number Heads Together to activities and results Study participant educate grade VII subjects lesson informatics at SMP N 5 Muara Bungo. Keywords: Cooperative Model, Number Heads Together, Activities and Learning Outcomes